Multisystem inflammatory syndrome in a child associated with COVID-19: a clinical case report - Kosmynina, N. S.; Dats-Opoka, M. I. (Zaporozhye Medical Journal, 2023)
Multisystem inflammatory syndrome in children (MIS-C) who contracted COVID-19 remains an urgent problem. Mortality due to this disease among children ranges from 0.8 % to 2.0 %. According to reports found in the literature, MIS-C can develop both in children who have experienced COVID-19 without clinical manifestations, and in those who have had a severe course of the disease. To date, there are no well-defined factors that allow predicting the risk of developing MIS-C in children after experiencing COVID-19, and the spectrum of clinical manifestations can be quite diverse. Aim: on the example of a specific case, to examine and analyze the features of the course and the range of diagnostic measures in children with MIS-C using an analytical method and a systemic approach. Materials and methods. The material was a clinical case of MIS-C, methods of instrumental diagnosis and objective analysis. The diagnosis of MIS-C was based on the WHO 2021 criteria for the diagnosis of MIS-C associated with COVID-19. Results. The clinical case of MIS-C associated with COVID-19 in a child with congenital thymus pathology that resulted in rapid, aggressive, and worsening multiple organ failure was studied. The manifestations were dominated by liver failure, respiratory failure, circulatory failure, and neurological deficiency, that led to the child’s death. Conclusions. Multisystem inflammatory syndrome in children associated with SARS-CoV-2 infection can lead to serious and life-threatening complications in previously clinically healthy children. Physicians need to be more alert to children of different age groups with manifestations of respiratory infections as potential COVID-19 and to test for its presence, which will subsequently allow timely identification of children with MIS-C associated with SARS-CoV-2. Considering the probable role of the thymus in the pathogenesis and course of MIS-C associated with SARS-CoV-2, we recommend an ultrasound examination of the thymus for all children under 3 years of age with confirmed COVID-19 and followed by examination of T-cellular response if changes are detected.